Reconstructing Curator Liability for Creditor Losses in Indonesian Bankruptcy Law - Made Warka; Indra Triantoro; Krinasi Nasution (jfpublisher, 2026)
Article 72 of Indonesian Bankruptcy Law obliges a curator to compensate losses arising from fault or negligence in managing and settling bankrupt assets, yet the provision does not define how fault should be measured, how causation should be proven, or what defense a curator may raise, which leaves both creditors and curators exposed to inconsistent outcomes. Prior studies on curator accountability have examined this problem mainly through procedural or criminal law lenses, leaving the underlying structure of Article 72 itself largely unexamined. This study addresses that gap by reconstructing Article 72 through the theory of the purpose of law and the theory of responsibility. Using normative legal research, the study applies the statutory, conceptual, philosophical, and comparative approaches, drawing on Indonesian bankruptcy law, comparative insolvency practice in selected jurisdictions, and relevant legal theory. The findings show that Article 72 correctly adopts liability based on fault but lacks the normative detail needed to apply that principle consistently, including graduated standards of fault, defined causation, and a good faith defense. Comparative practice in the Netherlands, the United Kingdom, the United States, and Germany confirms that fault-based liability, refined through professional oversight, remains the dominant model. The study concludes that reconstruction should refine rather than replace the fault-based principle, strengthening proportionality, legal certainty, and balanced protection between creditors and curators within Indonesia's bankruptcy system.